Functional state of the liver and endothelium in patients with menopausal metabolic syndrome - Irina A. Bulatova; Tatyana P. Shevlyukova; Inna L. Gulyaeva; Alexander A. Sobol; Valentina V. Khasanova (IP Berlin A.V., 2024)
Aim. To assess the functional state of the liver and endothelium in patients with menopausal metabolic syndrome, depending on the degree of obesity. Materials and methods. 70 patients with menopausal metabolic syndrome and obesity of varying degrees with an average age of 49.9±1.1 years and 30 practically healthy women without obesity and liver pathology with an average age of 47.3±2.6 years (comparison group) who were in the early postmenopausal period were examined. All women underwent biometric and laboratory-instrumental examination, including assessment of biometric indicators, determination of estradiol levels in the blood, biochemical markers of cytolysis and cholestasis, markers of endothelial dysfunction, assessment of microvascular tone reaction with calculation of the thermal vasodilation index, ultrasound examination of the liver and calculation of the Hepatic steatosis index (HSI). Results. All patients with menopausal metabolic syndrome had a genoid type of obesity and hypoestrogenism. The level of estradiol decreased more significantly during the transition to the 1st degree of obesity (p=0.001). According to ultrasound and the HSI index, signs of liver steatosis were found in all patients with menopausal metabolic syndrome. Functional liver tests were within the reference values, 13% had an increase in the level of alkaline phosphatase, more significant in the group with grade 3 obesity (p=0.034). Laboratory markers of endothelial dysfunction were significantly higher in patients with menopausal metabolic syndrome than in the comparison group. The muscular and neurogenic index of thermal vasodilation significantly decreased in women with grade 1 obesity compared to the group with "pre-obesity" (p=0.041 and 0.047). The lowest endothelial response was observed at the transition to the 1st degree of obesity in comparison with women with excess body weight. Conclusion. For patients with menopausal metabolic syndrome to assess the condition of the liver, it is recommended to conduct a comprehensive instrumental laboratory examination, including ultrasound examination of the liver, biochemical parameters and calculation of the steatosis index.